Engaging gen Y through social network sites / Vincent Wee Eng Kim and Vivien Wee Mui Eik @ Bee Jade - Wee, Vincent Eng Kim; Wee, Vivien Mui Eik @ Bee Jade (Research Management Institute (RMI), 2013)
Social networking sites are able to build on the interactive power of the Internet. This study attempts to discover the influence of social media on the present generation Y as consumers, their buying behaviour and to determine the roles that the social media plays as a popular medium to communicate a message. The findings of this research will provide clear and useful information to facilitate further research in similar fields of study. A set of questionnaire was administered to 200 students from ten selected institutions of higher learning in the Klang Valley. The respondents were asked about their current perceptions regarding their interaction with the social media websites and how these websites have influenced their purchasing behaviour which would enable further understanding about the social media. The respondents, responses show that, generally social media was used to seek useful information. They prefer to purchase in groups and the social media acts as a community platform to post and share their views. The respondents agreed that social media was more effective in finding information as compared to the use of the traditional mass media. Viral advertising in the form ofvideos are very appealing to them. Furthermore, social media also improves customers service and business networking.